Un aménagement de l'horaire pour une meilleure gestion des activités d'éducation scolaire et extra-scolaire : une question de partenariat, d'attentes et d'équité - Françoise Pasche Gossin; Éléonore Simon
This article discusses the scientific evaluation of a pilot project proposing a school time management measure allowing students who wish to leave the classroom to participate in music lessons given by professionals, or to benefit from special measures. This project, entitled "Supervised self-employment", should enable better management of school and extra-curricular activities through greater consideration and integration of the latter, as well as closer collaboration between the school and local cultural institutions. This article presents the perceptions of the different stakeholders induced by a reorganisation of the timetable. In this article, the research problem consists in answering the following research question : how do the different stakeholders perceive this reorganisation of the timetable in terms of reconciliation of in-school and out-of-school time, partnership and school justice ?